Integrity for the Enforcement in Forestry Perspective (Journal of Science, Technology and Innovation Policy, 2023)
The Forestry Department is one of the organizations that preserve national treasure assets consistently. As civil servants and staff of the Forestry Department organization, they must uphold the nature of trust, transparency, and responsibility and serve the public interest, which is the essence of the terms integrity and ethics. In other words, integrity and ethics in work and organization is not just an individual's self-involvement to provide for his own needs but rather involves good actions done at work and all of this is closely related to religious teachings and responsibility as a human being. The erosion of the value of integrity among civil servants in the Forestry Department will result in administrative errors and misconduct in the organization. Therefore, the practice and understanding of integrity and ethics must be implemented. The government has already paid serious attention to the problem of integrity and ethics among civil servants by launching Corruption Risk Management to develop the country in a balanced way. Realizing the importance of integrity as the core of quality staff development, this study discusses integrity in law enforcement from the perspective of the Forestry Department. In addition, this article describes the issues and challenges faced by the Forestry Department related to the lack of research on the implications of forestry law enforcement, especially shared values, makes it difficult for policy makers to determine conservation goals, methods and standards that are suitable for local acceptance. There is also a proposal to improvise on the integrity of the Forestry department by identifying the policy and revising the working procedures of area applications and creating an open tender system so that the selection of loggers is more transparent. Ultimately, it can improve the integrity of law enforcement from the perspective of the Forestry Department so that all employees and civil servants in an organization can practice it in order to improve the quality of superior and effective services.
Keywords: Integrity; workplace; policies related; Forestry Perspective